2023
DOI: 10.3389/fpubh.2023.1141757
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chinese healthcare organizations' innovative performance in the digital health era

Abstract: BackgroundHealthcare workers' relationship with industry is not merely an agent mediating between consumer and vendor, but they are also inventors of the interventions they exist to deliver. Driven by the background of the digital health era, scientific research and technological (Sci-tech) innovation in the medical field are becoming more and more closely integrated. However, scholars shed little light on Sci-tech relevance to evaluate the innovation performance of healthcare organizations, a distinctive feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Dependent variable-growth performance: recognising the limited applicability of traditional financial indicators to digital healthcare ventures, which often exhibit shorter lifespans and substantial initial investments, this construct focuses on metrics such as sales and profit growth rates as more indicative of success ( 65 , 78 ). The scale by Wang et al ( 91 ) was used, yielding a Cronbach’s α of 0.789, indicating good reliability.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Dependent variable-growth performance: recognising the limited applicability of traditional financial indicators to digital healthcare ventures, which often exhibit shorter lifespans and substantial initial investments, this construct focuses on metrics such as sales and profit growth rates as more indicative of success ( 65 , 78 ). The scale by Wang et al ( 91 ) was used, yielding a Cronbach’s α of 0.789, indicating good reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Ventures explore data resources’ potential through analytics, utilise big data to anticipate market trends and user needs, uncover new opportunities, and offer personalised, customised, and experiential digital healthcare services, culminating in exceptional service experiences ( 4 ). Ventures proficient in exploration thrive in the complex, dynamic, diverse, and uncertain digital healthcare landscape, ultimately improving growth performance ( 63 , 78 ). Ferreira et al ( 73 ) found that strategic alliances, as one of the main realisations of coopetition strategies, provide new ventures with access to additional resources and knowledge, enabling them to pursue business opportunities that would otherwise be unreachable.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations